1989
DOI: 10.1007/bf00431055
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis to Ginkgo biloba L.: relationship with urushiol

Abstract: A Ginkgo biloba L. fruit extract was prepared and purified. Three groups of guinea pigs were sensitized to the crude extract, anacardic acids 1, and cardanols 2 respectively, using the FCAT method, and the fourth group to urushiol using the epicutaneous route. Each group was tested for reaction to the primary sensitizer and to the different main aromatic compounds isolated from Ginkgo fruits. Anacardic acids were found to be good sensitizers, while cardanols failed to induce allergic contact dermatitis (ACD). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 8 publications
1
25
0
Order By: Relevance
“…84,111,112 Side effects from ginkgo appear to be relatively uncommon, but include headache, gastrointestinal tract upset, and skin allergy to the Ginkgo fruit. 48,49,53,61,[113][114][115] Of these, headache is the most common, and it is best prevented by starting with a low dose and gradually titrating to the required dose. Many researchers have suggested that ginkgo theoretically may potentiate other anticoagulants or increase bleeding time; however, these effects rarely have clinically significant implications.…”
Section: Ginkgomentioning
confidence: 99%
“…84,111,112 Side effects from ginkgo appear to be relatively uncommon, but include headache, gastrointestinal tract upset, and skin allergy to the Ginkgo fruit. 48,49,53,61,[113][114][115] Of these, headache is the most common, and it is best prevented by starting with a low dose and gradually titrating to the required dose. Many researchers have suggested that ginkgo theoretically may potentiate other anticoagulants or increase bleeding time; however, these effects rarely have clinically significant implications.…”
Section: Ginkgomentioning
confidence: 99%
“…They were, however, not supported by a recent study of the ginkgolic acids found in Ginkgo fruits and urushiol from Toxicodendron [146]. Patch testing can be performed with fruit pulp in 1% acetone [144].…”
Section: Ginkgoaceae (Maidenhair Family)mentioning
confidence: 90%
“…Experiments in guinea-pigs showed that ginkgolic acids are really the sensitizers in these animals, but no cross-reactions could be detected between Ginkgo and Rhus. In addition, the intermediate 16 was shown not to be a sensitizer [17]. In this case, the active form is still unknown although it may be supposed to be a quinone intermediate.…”
Section: Pro-haptenesmentioning
confidence: 96%